Personality moderates the links of social identity with work motivation and job searching - Baay, Pieter E.; van Aken, Marcel A. G.; van der Lippe, Tanja; de Ridder, Denise T. D. (Frontiers in Psychology, 2014)
Work motivation is critical for successful school-to-work transitions, but little is known about its determinants among labor market entrants. Applying a social identity framework, we examined whether work motivation and job searching are social-contextually determined. We expected that some job seekers are more sensitive to contextual influence, depending on their personality. Mediation analyses on 591 Dutch vocational training students indicate that the perception of more positive work norms in someone’s social context was related to higher levels of intrinsic motivation, which in turn predicted higher preparatory job-search behavior and job search intentions. Multi-group analysis shows that perceived work norms more strongly predict work motivation among overcontrollers compared to resilients and undercontrollers. In conclusion, work motivation and job searching appear contextually determined: especially among those sensitive to contextual influence, people seem to work when they believe that is what people like them do.